Metabolic Basis and Clinical Evidence for Skin Lightening Effects of Thiol Compounds - Yong Chool Boo (MDPI AG, 2022)
Melanin pigment is a major factor in determining the color of the skin, and its abnormal increase or decrease can cause serious pigmentation disorders. The melanin pigment of the skin is divided into light pheomelanin and dark eumelanin, and a big difference between them is whether they contain sulfur. Melanin synthesis starts from a common reaction in which tyrosine or dihydroxyphenylalanine (DOPA) is oxidized by tyrosinase (TYR) to produce dopaquinone (DQ). DQ is spontaneously converted to leukodopachrome and then oxidized to dopachrome, which enters the eumelanin synthesis pathway. When DQ reacts with cysteine, cysteinyl dopa is generated, which is oxidized to cysteinyl DQ and enters the pheomelanin synthesis pathway. Therefore, thiol compounds can influence the relative synthesis of eumelanin and pheomelanin. In addition, thiol compounds can inhibit enzymatic activity by binding to copper ions at the active site of TYR, and act as an antioxidant scavenging reactive oxygen species and free radicals or as a modulator of redox balance, thereby inhibiting overall melanin synthesis. This review will cover the metabolic aspects of thiol compounds, the role of thiol compounds in melanin synthesis, comparison of the antimelanogenic effects of various thiol compounds, and clinical trials on the skin lightening efficacy of thiol compounds. We hope that this review will help identify the advantages and disadvantages of various thiol compounds as modulators of skin pigmentation and contribute to the development of safer and more effective strategies for the treatment of pigmentation disorders.